Effectiveness of 3P Implementation (People, Process, Physical Evidence) And Company Performance At Different Levels Of Complexity And Divergence - Anggoro Destu Adhi (Institute of Computer Science (IOCS), 2021)
The aim of this research is to know the differences of the level of complexity and divergence, the different effektiveness of 3P’s and the performance of two workshops (an authorized service station of motorcycle and an unauthorized one). The techniques used to collect data were: 1) interview, to know the general map of the company, 2) questionaires, to know data of complexity and divergence of the company, scores of perception concerning the effectiveness of 3P’s, 3) documentation, to know the daily total numbers of service within a year. The data analysing techniques used were ; the different percentage test use to know the different of level the complexity and divergence, the U Mann-Whitney Test used to know the different of 3P’s effectiveness and performances. The research found that : 1) there was a different of the level of complexity and divergence between an authorized service station of motorcycle and the unauthorized one. In the level of the different of complexity was 16,67%, the authorized service station has relatively higher level of complexity than unauthorized one. For this level of divergence is 10% and the authorized service station has relatively lower level of divergence than unauthorized one. 2) there was no different of 3P’s effectiveness between both service stations, at the variable people there was no diferent with z=-0,225 (p>0,05) and at the variable process there was no diferent with z=-0,122 (p>0,05) then at the variable physical evidence there was no diferent with z=-0,160 (p>0,05). 3) there was a different performance between an authorized service station and an unauthorized one. As specialy in giving minor service between the authorized service station and the unauthorized one namely z =-6,10 (p<0,05) and for the medium service, z = -6,786 (p<0,05) while for the major service,z = - 6,675 (p<0,05) and for the whole service between the authorized service station and unauthorized one the diferent was z = - 6,675 (p<0,05), but the authorized service station had much higher performance level than the unauthorized one in each service and doing full service.